A low‐carbon dispatch of power system incorporating active distribution networks based on locational marginal emission. Issue 1 (23rd August 2017) - Hu, Jingzhe; Jiang, Chuanwen; Cong, Hao; He, Yang
Abstract : Involvement of active distribution networks (ADNs) in emission management can give full play to the carbon‐reduction potential of distributed generations (DGs) and demand response. With the development of smart grid, low‐carbon coordinated scheduling of power system with ADNs will become a new trend. A bilevel dispatch model based on locational marginal emission (LME) is proposed to achieve carbon reduction from both generation and load sides. The main grid dispatch is a problem of dynamic optimal power flow aiming at reducing both the operating and emission costs, in which LME under AC condition is adopted to calculate the carbon emission produced by node power. The ADN level is the DG generation schedule with the objective of minimizing both the cost and system emission based on LME. The main grid and ADNs interact and cooperate with each other by locational marginal price (LMP) and LME to cut the carbon pollution. Simulation results in a modified IEEE 30‐bus system and an IEEE 118‐bus system show that compared with the traditional LMP‐based coordinated scheduling, the bilevel dispatch model based on LME can reduce carbon emission effectively and promote ADNs' participation in system carbon emission management. © 2017 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.